1984
DOI: 10.1099/00221287-130-5-1227
|View full text |Cite
|
Sign up to set email alerts
|

Exo-(l->3)- -glucanase, Autolysin and Trehalase Activities during Yeast Growth and Germ-tube Formation in Candida albicans

Abstract: Exo-(1----3)-beta-glucanase, beta-glucosidase, autolysin and trehalase were assayed in situ in Candida albicans during yeast growth, starvation and germ-tube formation. Cell viability, germ-tube formation, intracellular glucose-6-phosphate dehydrogenase and beta-glucosidase were unaffected in cells incubated in 0.1 M-HC1 for 15 min at 4 degrees C. However, in situ trehalase, (1----3)-beta-glucanase and autolysin activities in acid-treated cells decreased by 95, 50 and 35% respectively, indicating that these en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…Recently we found that exo-( 1 -, 3)-P-glucanase was secreted and exported in C. albicans during germ-tube formation but negligible enzyme was released into the yeast growth medium (Ram et al, 1984). It is suggested that the germ-tube wall is more porous than that of yeast cells and consequently export of enzymes is facilitated by the formation of hyphae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we found that exo-( 1 -, 3)-P-glucanase was secreted and exported in C. albicans during germ-tube formation but negligible enzyme was released into the yeast growth medium (Ram et al, 1984). It is suggested that the germ-tube wall is more porous than that of yeast cells and consequently export of enzymes is facilitated by the formation of hyphae.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular distribution of N-acetylglucosaminidase was determined by measuring in siru enzyme activity before and after treatment of intact cells with 0-1 M-HCl (Ram et al, 1984). Washed cells were resuspended in 0.1 M-HCI at 4 "C, incubated for 15 min, neutralized with NaOH and washed three times with the potassium phosphate buffer.…”
Section: P a S U L L I V A N A N D Othersmentioning
confidence: 99%
“…Acid treatment (Ram et al, 1984) of C . albicans cells did not inactivate the in situ proteinase activity but a crude proteinase ycaB preparation was inactivated at pH 1.5 and 0 "C. The in situ proteinase activity was not increased by permeabilizing (Ram et al, 1984) cells. Intact cells are also permeable to Leu-Nna (Montes & Constantine, 1968).…”
Section: Cellular Location Of Enzymesmentioning
confidence: 84%
“…Candida albicans (ATCC 10261) was grown as described previously (Farley et al, 1986) and germ-tube formation induced with starved yeast cells and N-acetylglucosamine at 37 "C (Ram et al, 1984). Starved cells incubated at 28 "C under these conditions retained the yeast morphology and are referred to as yeast control cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation